2016
DOI: 10.2337/db16-0405
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics of the Human Endocrine Pancreas

Abstract: Human pancreatic islets consist of multiple endocrine cell types. To facilitate the detection of rare cellular states and uncover population heterogeneity, we performed single-cell RNA sequencing (RNA-seq) on islets from multiple deceased organ donors, including children, healthy adults, and individuals with type 1 or type 2 diabetes. We developed a robust computational biology framework for cell type annotation. Using this framework, we show that α- and β-cells from children exhibit less well-defined gene sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
446
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(476 citation statements)
references
References 37 publications
27
446
3
Order By: Relevance
“…Approximately one-third (340/978) of cells expressed more than one marker gene; these were removed from subsequent analysis due to concerns that these represent two vertically stacked cells in a given capture site (for details, see Methods). Similar ratios of potential stacked cells have been reported in other studies using the Fluidigm C1 platform to capture mouse (Xin et al 2016) and human islet cells (Wang et al 2016). Collectively, these single-cell data capture transcriptome profiles representing each of the major and minor pancreatic endocrine and exocrine cell types.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Approximately one-third (340/978) of cells expressed more than one marker gene; these were removed from subsequent analysis due to concerns that these represent two vertically stacked cells in a given capture site (for details, see Methods). Similar ratios of potential stacked cells have been reported in other studies using the Fluidigm C1 platform to capture mouse (Xin et al 2016) and human islet cells (Wang et al 2016). Collectively, these single-cell data capture transcriptome profiles representing each of the major and minor pancreatic endocrine and exocrine cell types.…”
Section: Resultssupporting
confidence: 62%
“…We therefore sought to validate our observed celltype-specific differences in T2D islets using these independent data sets (Wang et al 2016;Segerstolpe et al 2016). We found that 54/77 genes and 32/171 were also significantly up-and down-regulated, respectively, in T2D beta cells in these studies (P < 0.05, two-sided Wilcoxon rank-sum test) (Supplemental Fig.…”
Section: Wwwgenomeorgmentioning
confidence: 80%
See 1 more Smart Citation
“…GLP1R mRNA levels were similar in juvenile and adult human islets (Figure 2A), suggesting that human β cell GLP-1R expression is not age-dependent. Moreover, in FACSisolated islet cell subsets, GLP1R mRNA was principally expressed in β cells and was very low, or not detectable, in α cells (Supplemental Figure 2, A-C), consistent with prior findings (10,(31)(32)(33)(34)(35).…”
Section: Introductionsupporting
confidence: 78%
“…Haploinsufficiency of PAX6 in humans does interfere with β cell function and leads to abnormal glucose homeostasis, suggesting that even partial effects on PAX6 expression may have glycemic consequences (27,28). We note, however, that in expression profiles obtained from type 2 diabetic donors using both whole islets and single β cells, no significant reduction in PAX6 expression levels was observed compared with levels detected in nondiabetic donors (7,63,64). This may be attributed to euglycemia in those patients.…”
Section: Pax6 Directly Regulates Transcription From the Insulin Genecontrasting
confidence: 41%